Social protection and sustainable poverty reduction: Experimental evidence from Bangladesh - Ahmed, Akhter; Hidrobo, Melissa; Hoddinott, John F.; Koch, Bastien; Roy, Shalini; Tauseef, Salauddin (International Food Policy Research Institute, 2020)
Social protection programs are primarily focused on influencing household behavior in the short term, increasing consumption to reduce poverty and food insecurity, and promoting investments in human capital. A large body of evidence across numerous settings shows that cash and food transfer programs are highly effective in doing so. However, there is growing interest in understanding the extent to which such programs can help households stay out of poverty in the longer term, specifically after transfers end. We bring new evidence to this question, re-interviewing Bangladeshi households that participated in a well-implemented randomized social protection intervention four years after it ended. We find that combining transfers, either cash or food, with behavior change communication activities sustainably reduced poverty. Cash transfers alone had sustainable effects, but these were context-specific. The beneficial impacts of food transfers did not persist four years after the intervention finished.